2013
DOI: 10.1007/s12032-013-0687-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidences of diabetes and prediabetes among female adult breast cancer patients after systemic treatment

Abstract: Patients with cancer frequently show glucose intolerance. This study is to estimate the status of total diabetes and prediabetes in breast cancer patients after systemic treatment through an oral glucose tolerance test (OGTT) in China. All the 119 breast cancer patients more than 3 months after systemic treatment with surgery and chemotherapy participated in the study. All the patients without the diagnosis of diabetes underwent OGTT, and fasting and 2-h glucose levels were measured to identify undiagnosed dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
10
1
1
Order By: Relevance
“…Among the diabetic states, 63% of the patients were nondiabetic, 26% were prediabetic, and 9% were diabetic. These percentages are lower than previous studies, which found that 44% of patients with cancer had prediabetes, and from 19% (Bhatnagar et al, 2014) to 22% (Ji et al, 2013) of patients had diabetes. Reasons for these differences are not readily apparent and warrant additional investigation.…”
Section: Discussioncontrasting
confidence: 79%
“…Among the diabetic states, 63% of the patients were nondiabetic, 26% were prediabetic, and 9% were diabetic. These percentages are lower than previous studies, which found that 44% of patients with cancer had prediabetes, and from 19% (Bhatnagar et al, 2014) to 22% (Ji et al, 2013) of patients had diabetes. Reasons for these differences are not readily apparent and warrant additional investigation.…”
Section: Discussioncontrasting
confidence: 79%
“…Chemotherapy treatment may cause diabetes to develop earlier in susceptible women. Weight gain, estrogen suppression, and glucocorticoids are risk factors [11161718]. …”
Section: Hyperglycemia In Cancer Patientsmentioning
confidence: 99%
“…However, in those studies, OGTT were not performed in the entire study population; therefore, the true incidence of undiagnosed diabetes may have been underestimated. Therefore, in the previous research, we firstly studied the status of total diabetes and prediabetes in breast cancer patients after systemic treatment through OGTT in Southwest of China and found that the overall incidences of total diabetes and prediabetes were 21.8% and, 43.7%, respectively; about 80% of the diabetes were previously undiagnosed; about 80.0% of the cases of undiagnosed diabetes and, prediabetes met the criteria for elevated 2-hour plasma glucose levels through OGTT but not the criteria for elevated fasting glucose levels [16].…”
Section: Discussionmentioning
confidence: 99%
“…The previously reported findings have not all been consistent, owing to methodological differences in sampling and to differences in the criteria used to define diabetes [15]. Furthermore, the prevalences of diabetes and prediabetes were probably under estimated in these studies because 2-hour oral glucose-tolerance tests (OGTT) were not performed in all participants [16]. It has been reported that isolated hyperglycemia 2 hours after glucose loading is common among Asian diabetic patients [17].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation